Effects of psychosocial work characteristics on hair cortisol – findings from a post-trial study. (4th July 2017) - Herr, Raphael M.; Barrech, Amira; Gündel, Harald; Lang, Jessica; Quinete, Natalia Soares; Angerer, Peter; Li, Jian
Abstract: Prolonged work stress, as indicated by the effort-reward imbalance (ERI) model, jeopardizes health. Cortisol represents a candidate mechanism connecting stress to ill health. However, previous findings appear inconclusive, and recommendations were made to assess work stress at multiple time points and also to investigate ERI (sub-)components. This study therefore examines the effects of two single time points, as well as the mean and change scores between time points of ERI and its components on hair cortisol concentration (HCC), a long-term cortisol measurement. Participants were 66 male factory workers (age: 40.68 ± 6.74 years; HCC: 9.00 ± 7.11 pg/mg), who were followed up after a stress management intervention (2006–2008). In 2008 (T1) and 2015 (T2), participants completed a 23-item ERI questionnaire, assessing effort, the three reward components (esteem, job security, job promotion) and over-commitment. In 2015, participants also provided a 3-cm hair segment close to the scalp for HCC analysis, as well as information on relevant confounders (i.e. medication intake, age, work characteristics, socioeconomic and lifestyle factors, number of stressful life events). Linear regressions revealed hardly any cross-sectional or longitudinal effect of ERI and its components on HCC. Only the change scores between T1 and T2 of job security were negatively associated with lower HCC in unadjusted (β = −.320; p = .009) and adjusted (β = −.288; p = .044) models. In this study, only a decrease of perceived job security over time was significantly associated with higher HCC, and other predictors were not related to this outcome. Especially after correction for multiple testing, this study revealed just a weak association of different psychosocial work measurements with HCC. Lay summary This study showed that an increase in perceived job insecurity is correlated with higher levels of the stress hormone cortisol. The higher levels of cortisol might represent a biological explanation for the negative health effects of job insecurity. The association was, however, relatively low, and more and more voices are questioning whether cortisol in hair is a reliable marker for perceived work stress.